(untitled) (Proceedings of Southern Federal University. Philology, 2021)
Natalia D. Osipova (Samara, Russian Federation) The article characterizes the names of sweets, including anthroponyms, from the point of view of syntactic structure. Four groups of pragmatonyms are analyzed. The first group includes names that formally correspond to Russian anthroponymic formulas (one-, two- and three-component), which determines the novelty of the research. Among the one-component formulas, the formulas “Name” (full anthroponym) and “Surname” are highlighted. Within the framework of the subgroup of two-component formulas, the names built according to the models “First name + Middle Name” and “First name + Last name” have been studied. The nominations of this group in some cases reflect the imitation of the anthroponymic formula (with semantic digressions) as a result of the onimization process. The second group of pragmatonyms was made up of one-word anthroponyms in a hypocoristic or deminutive form. The third group is represented by phrases with a compositional and subordinate (on the basis of agreement, management and adherence) communication. Substantive combinations, including applications, are built on the basis of agreement. Combinations with two types of communication (compositional and subordinate) are classified. The fourth group includes pragmatonyms – sentences. Within the framework of this group, the names of sweets are considered, which are, in their structure, common and uncommon simple sentences. Key words: pragmatonym, anthroponym, syntax, anthroponymic formula, phrase, sentence. DOI 10.18522/1995-0640-2021-2-77-86